Analisis Bahasa Melayu dalam Cerita Rakyat Melayu Riau: Kajian Morfologi - Erma Aryanti, Ade; Mukhlis, Muhammad (UIR Press, 2024)
The Bengkalis dialect of Riau Malay is unique. In Indonesian, the prefix ter- meets basic words that start with /l/, so there will be a conservation of phonemes, for example ter- + then = too